ANALISIS PENGARUH IKLAN, CELEBRITY ENDORSER DAN CITRA MEREK TERHADAP MINAT BELI WARDAH KOSMETIK - ARIFA QONITA (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
ABSTRACT The need for women to look as beautiful as she wants creates a huge market potential in the cosmetics industry. So wardah is present to answer the dream of all women, of all skin types and skin color. Wardah has the tagline